Complete mitochondrial genome of the Yellow-bellied Tit Parus venustulus (Passeriformes, Paridae). (2nd September 2016) - Li, Xuejuan; Huang, Yuan; Lei, Fumin
Abstract: The circular mitochondrial genome of Yellow-bellied Tit Parus venustulus is 16, 778 bp in length, containing 13 protein-coding genes (PCGs), 2 ribosomal RNA genes, 22 transfer RNA (tRNA) genes, and a putative control region. All of the genes are encoded on the H-strand, except for one PCG ( nad6 ) gene and eight tRNA genes ( tRNA Gln, tRNA Ala, tRNA Asn, tRNA Cys, tRNA Tyr, tRNA Ser (UCN), tRNA Pro and tRNA Glu ). All of these PCGs are initiated with ATG, except for cox1, which began with GTG, while stopped by six types of stop codons. All tRNA genes have the potential to fold into typical clover-leaf structure, with exception of the tRNA Ser (AGY) which lacks the DHU stem.